Self-compassion in Women with breast cancer: Self-compassion pada perempuan pengidap kanker payudara - Fransiska Klara Olivia Pepe; Tience Debora Valentina (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Women with breast cancer experience psychological impacts, such as fear, anxiety, and even depression. Women with breast cancer need to adjust themself psychologically to go through life. Self-compassion helps individuals with chronic diseases to adapt to the psychological impact. This research aims to explore self-compassion in women with breast cancer. This research found that participants tend to turn judgment into acceptance of their body changes as an impact of surgery, warm social relationships, and an outlook of not wanting to look weak. There was an awareness of balanced and exaggerated responses, along with forms of coping with approaching and avoiding problems. This research contributes to developing interventions for developing self-compassion among women with breast cancer.